Léncak: Ruang Sosial-Keagamaan Tokoh Agama Perempuan Madura - Jannah, Hasanatul; Ida, Rachmah (FIKRAH, 2019)
This research explores and interprets léncak as one of the treasures of the treasures of the ancestors' heritage and can be produced from generation to generation. The wealth stored on the island of Madura, both in the form of views, ethics, culture and wealth of objects containing social values and meanings for the religious life of the Madurese community, especially for female religious leaders of Madura. One of these objects was named léncak, because it was on this level that the female religious leaders spent a lot of time formulating the problems of their people, thus becoming intermediaries to the public space. This study uses a phenomenological approach, because it wants to reveal the social significance of the one used by religious leaders of Madurese women in carrying out their religious social roles. This research found that it must be a meaningful, inspirational, facilitative space for the continuation of religious negotiations as well as opening the public space for female religious leaders with their communities